1987
DOI: 10.1007/bf00128891
|View full text |Cite
|
Sign up to set email alerts
|

Improving personnel evaluations through professional standards

Abstract: This article is a progress report on the Project to Develop Standards for Evaluations of Educational Personnel, a three-and-a-half-year project being conducted by the Joint Committee on Standards for Educational Evaluation. The overall goal of the project is to help improve systems for evaluating teachers, educational administrators, professors, and other educators, and to increase the educational benefits of personnel evaluations. The main contribution from this project will be professionally defined standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

1988
1988
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 2 publications
0
4
0
1
Order By: Relevance
“…A third argument against principals' evaluations of teachers is that principals are not able to discriminate among teachers, they fail to recognize exemplary teaching and as a result they award similar and inflated ratings (Haefele, 1992). The consequences of non-discrimination are serious, because inaccurate teacher evaluations allow unqualified teachers to assume teaching positions and make it difficult for education systems to remove incompetent and unproductive teachers (Haefele, 1992; Joint Committee on Standards for Educational Evaluation, 1988;Stufflebeam and Brethower, 1987). However, recent studies have shown that principals are quite good at identifying teachers who produce the largest and smallest standardized achievement gains, but are less able to distinguish among teachers in the middle of the distribution (Jacob and Lefgren, 2008).…”
Section: Teacher Evaluations By Principalsmentioning
confidence: 99%
“…A third argument against principals' evaluations of teachers is that principals are not able to discriminate among teachers, they fail to recognize exemplary teaching and as a result they award similar and inflated ratings (Haefele, 1992). The consequences of non-discrimination are serious, because inaccurate teacher evaluations allow unqualified teachers to assume teaching positions and make it difficult for education systems to remove incompetent and unproductive teachers (Haefele, 1992; Joint Committee on Standards for Educational Evaluation, 1988;Stufflebeam and Brethower, 1987). However, recent studies have shown that principals are quite good at identifying teachers who produce the largest and smallest standardized achievement gains, but are less able to distinguish among teachers in the middle of the distribution (Jacob and Lefgren, 2008).…”
Section: Teacher Evaluations By Principalsmentioning
confidence: 99%
“…Proper use of the Standards can provide assurances of quality control to stakeholders and can support improvement in the overall personnel evaluation process (Stufflebeam & Brethower, 1987;Stufflebeam & Sanders, 1990).…”
Section: Technically Sound Evaluation Systemsmentioning
confidence: 99%
“…La aplicación razonable y eficiente de estas normas para la evaluación de profesores fue un tema de interés, trabajo y producción científica para un gran experto en evaluación como Stufflebeam y algunos de sus colaboradores (Stufflebeam & Brethower, 1987;Stufflebeam & Sanders, 1990).…”
Section: Normas En La Evaluación De Profesoresunclassified